THE POLITICAL CULTURE OF ROMANIA - STOENESCU, Roxana-Alice (Studia Universitatis Babes-Bolyai Studia Europaea, 2021)
In addition to Romania's economic backwardness, the experiences of repressive political culture have contributed to restricting society's ability to act by impairing the development of its own identity for centuries. The background to the emergence of totalitarian regimes can be derived from the context of the European modernization processes, which have gripped the whole of Europe through the industrialization and consequently secularization and rationalization process. By reproducing these processes, political situations and the experiences of Romanian society on which they are based, reveals the significance of their political culture. The aim is to put together the political culture of modern Romanian society in order to ultimately understand what the problems are for their current political consciousness.